Spatial and temporal based deforestation proclivity analysis on flood events with applying watershed scale (case study: Lasolo watershed in Southeast Sulawesi, Central Sulawesi, and South Sulawesi, Indonesia) - Ramadhan, Cahyadi; Dina, Ruslanjari; Nurjani, Emilya (International journal of disaster risk reduction, 2023)
Flood often occurs triggered by the failure of the system in the hydrological cycle such as deforestation in the nearby watershed upstream. Analysis of flood handling in a watershed area requires spatial and temporal study to reveal more complex results. This study aims to analyze the development of deforestation and flood events in the Lasolo watershed and to investigate deforestation proclivity. Purposive sampling was applicable as the method to analyze the data for the case study. Premier data include quantitative data related to deforestation and flood events in the study area whilst the secondary data was obtained from relevant institutions. Moreover, data analysis techniques contain quantitative analysis (i.e. spatial-temporal analysis, descriptive-quantitative analysis), and inferential statistic analysis. The result proves three anomalous patterns in relation to deforestation nearby downstream, middle, and upstream of the Lasolo watershed and flood events around the downstream area or in North Konawe Regency, South-East Sulawesi Province. The first pattern reveals sufficient stability on the deforested land surface in 2006–2012 towards rain intensity when flooding, The second pattern claims a more generic response of the land surface to the rainfall in 2012–2017. The third pattern in 2018–2020 results relatively sensitive response against rain particularly when a flood occurs.